S51 MTOR regulates TGF-β induced pro-fibrotic gene expression in primary human lung fibroblasts. (15th November 2016) - Woodcock, HV; Eley, JD; Nanthakumar, C; Maher, TM; Mercer, PF; Chambers, RC
Abstract : Introduction: TGF-β is a major pro-fibrotic cytokine with a critical role in the pathogenesis of idiopathic pulmonary fibrosis (IPF). TGF-β drives fibroblast to myofibroblast differentiation and extracellular matrix synthesis. mTOR plays a critical role in regulating protein translation and is the catalytic subunit of two functionally distinct complexes, mTORC1 and mTORC2, which have differential sensitivities to rapamycin. The aim of this study was to delineate mTOR signalling in response to TGF-β in human lung fibroblasts and investigate the role of the mTOR pathway in TGF-β mediated myofibroblast differentiation and collagen synthesis. Methods: All human samples were obtained with informed, signed consent and with research ethics committee approval. Primary human lung fibroblasts (pHLFs) were grown from explant cultures. Cells were pre-incubated with varying concentrations of inhibitor before stimulation with TGF-β 1ng/ml. Collagen biosynthesis and αSMA expression were measured by a high-content imaging based molecular crowding assay. Gene expression was measured by qPCR. Western blots were performed to assess mTOR substrate phosphorylation. Results: TGF-β was found to stimulate the delayed and sustained induction of mTOR signalling in pHLFs and this signalling pathway was critical for mediating the late peak in TGF-β induced pro-fibrotic gene expression. Accordingly, active-site mTOR inhibition exerted pronounced inhibitory effects on pHLF collagen biosynthesis and myofibroblast differentiation. The induction of mTOR signalling in response to TGF-β was dependent on the canonical Smad pathway. In addition, potent and selective pharmacological agents demonstrated that TGF-β induced mTOR signalling was independent of PI3K/Akt activity, suggesting that mTOR is not activated through the prototypical linear PI3K/Akt axis downstream of TGF-β. Moreover, rapamycin-resistant mTOR signalling was found to be critical for TGF-β induced pro-fibrotic gene expression in pHLFs. Conclusion: mTOR is a an important pro-fibrotic signalling node downstream of TGF-β and a potential target for therapeutic intervention in IPF.